Proposta de implantação do modelo de análise do processo interativo (MAPI) na atenção básica para idosos com depressão - Pereira, Francisca Leneide Gonçalves (2019)
Introduction: Depression in the elderly is a serious health problem and may be associated with comorbidities, affecting the quality of life of this population. Some symptoms are confused with the signs evidenced in the aging process, which makes it difficult for some professionals to diagnose, leading to late treatment. The role of nurses in primary care concerns challenges in their daily lives in the construction of interpersonal relationships, based on dialogue, listening, humanization and respect. As a systematization tool for nursing care, the use of the Interactive Process Analysis Model that contemplates the nursing process through interactions with the person who needs help to facilitate the diagnosis of the situation is highlighted. health action planning. Thus, it is important to build a nursing care protocol for the elderly with depression, based on the Interactive Process Analysis Model, aiming at the knowledge of the health needs of the elderly with depression, the development of a tool that facilitates the work process of the nurse and, consequently, the improvement of the quality of life of the elderly with depression. Objectives: to highlight the scientific production on depression in the elderly assisted in primary health care; to apply the Interactive Process Analysis Model in elderly with depression treated in primary care; indicate a Proposal for the Implementation of the Interactive Process Analysis Model in Primary Care for Depressed Elderly. Method: This is a methodological study, with the following steps: research in national and international databases enabling a situational survey in scientific publications on depression in the elderly treated in primary health care, to conduct an integrative review on the thematic approached; An empirical investigation with ten elderly with depression assisted in primary health care, using the Interactive Process Analysis Model for nursing diagnoses, the elaboration of a Nursing Care Protocol for Depressed Elderly. Results and Discussion: In the first stage, 19 articles on the theme were highlighted, highlighting the researchers' concern about the training of professionals, in view of the transformations of the elderly population in the world. Therefore, the second stage was performed with ten elderly diagnosed with depression. Using the interactive model, three moments were performed, which enabled the identification of nursing diagnoses and interventions for each of them. The nursing evaluation is aimed at providing feedback on previous therapeutic proposals. In the third stage, it was proposed the implementation of the Interactive Model during nursing care to the elderly with depression attended at the Basic Health Units in Cajazeiras. Conclusion: This study proposes to implement the Interactive Process Analysis Model in primary care for elderly with depression, considering the use of Nursing Care Systematization in the professional practice of nurses in the context of Primary Health Care.